2021
DOI: 10.1038/s41598-021-85593-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of mutational and clinicopathologic characteristics of poorly differentiated colorectal neuroendocrine carcinomas

Abstract: Poorly differentiated neuroendocrine carcinoma (NEC) is a rare subtype of colorectal cancer (CRC). This study aimed to investigate clinicopathologic characteristics of colorectal NECs and elucidate genomic differences and similarities between colorectal NECs and colorectal adenocarcinomas (ACs). A total of 30 colorectal NECs were screened for frequently identified CRC oncogenic driver genes by targeted next-generation sequencing of 382 genes. The median age of the patients was 67 years (range, 44 to 88 years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
1
21
2
Order By: Relevance
“…Similarly, the mutation frequency of APC was 36.7%, 53% and 71%, respectively, with the mean at 53.6%, and all three studies focused on NEC [22,26,27]. These studies also reported the KRAS mutation frequency of 25%, 36%, and 53.3%, respectively [22,26,27], with a mean of 38.1%. RB1 mutation has been identified in NET, and it was reported to be co-mutated with TP53 in small cell lung cancer, which is regarded as a cancer with neuroendocrine cell origin [28].…”
Section: The Mutational Landscape Of Rectal Netsmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, the mutation frequency of APC was 36.7%, 53% and 71%, respectively, with the mean at 53.6%, and all three studies focused on NEC [22,26,27]. These studies also reported the KRAS mutation frequency of 25%, 36%, and 53.3%, respectively [22,26,27], with a mean of 38.1%. RB1 mutation has been identified in NET, and it was reported to be co-mutated with TP53 in small cell lung cancer, which is regarded as a cancer with neuroendocrine cell origin [28].…”
Section: The Mutational Landscape Of Rectal Netsmentioning
confidence: 82%
“…It exhibited a huge fluctuation, which may be caused by different ratios of samples with distinct pathological grades. For example, the studies reporting 10.1% and 14.3% mutational frequency focused on G1 and G2 NETs [19,25], while the studies reporting 43%, 57%, and 61% often focused on NEC [22,26,27]. Similarly, the mutation frequency of APC was 36.7%, 53% and 71%, respectively, with the mean at 53.6%, and all three studies focused on NEC [22,26,27].…”
Section: The Mutational Landscape Of Rectal Netsmentioning
confidence: 98%
See 3 more Smart Citations